2019
DOI: 10.1016/s0140-6736(19)30606-3
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of obesity and overweight in Palestine: a systematic review

Abstract: Background Overweight and obesity are increasing at an alarming rate in developed countries and developing countries like Palestine. Obesity (body mass index [BMI]30) and overweight (BMI 25•0−29•9) predispose to several non-communicable diseases (NCDs) such as diabetes, hypertension, and cardiovascular diseases. Obesity prevalence studies in different age groups and locations across Palestine are very varied in their methods, participants, settings, or results. We aimed to assess the prevalence of obesity and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 0 publications
0
12
0
Order By: Relevance
“…Obesity is a common disease of clinical and public health importance [2,3,6]. However, studies concerning obesity and central obesity among Palestinians are scarce [40][41][42][43]. This study aimed to investigate the risk of tobacco smoking and ED consumption and obesity among Palestinian university students from ANNU.…”
Section: Discussionmentioning
confidence: 99%
“…Obesity is a common disease of clinical and public health importance [2,3,6]. However, studies concerning obesity and central obesity among Palestinians are scarce [40][41][42][43]. This study aimed to investigate the risk of tobacco smoking and ED consumption and obesity among Palestinian university students from ANNU.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the prevalence of overweight and obesity was also studied by a recent systematic review of 38 articles in the OPT (Elessi & Albaraqouni, 2019). The prevalence of overweight and obesity was 15% and 6%, respectively, among children, 30% and 18%, respectively, among adults, and 40% and 49%, respectively, among people with noncommunicable diseases (Elessi & Albaraqouni, 2019). These rates are due to changes in physical activity, dietary habits, and shifting from traditional to Western lifestyles.…”
Section: Discussionmentioning
confidence: 99%
“…Among adults 18 years and older, 64% of males and 69.5% of females were overweight, and 26.2% of males and 38.8% of females were living with obesity in 2015 (Global Nutrition Report, 2018). Additionally, the prevalence of overweight and obesity was also studied by a recent systematic review of 38 articles in the OPT (Elessi & Albaraqouni, 2019). The prevalence of overweight and obesity was 15% and 6%, respectively, among children, 30% and 18%, respectively, among adults, and 40% and 49%, respectively, among people with noncommunicable diseases (Elessi & Albaraqouni, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of obesity among school students aged 13–17 years in the Occupied Palestinian Territories (OPT) has been reported to be 27.8% in the village of Tarqumia near Hebron (Ghrayeb et al, 2013). In a review by Elessi and Albaraqouni (2019), the prevalence of obesity and overweight was reported as 18% and 30% in adults, and 49% and 40% in adults with chronic diseases in OPT, indicating the seriousness of the problem. Cardiovascular disease and cancer are the leading causes of death in OPT according to previous reports (Abu-Rmeileh et al, 2008).…”
Section: Introductionmentioning
confidence: 99%